2011
DOI: 10.3233/ch-2010-1385
|View full text |Cite
|
Sign up to set email alerts
|

Association between high red blood cell distribution width and metabolic syndrome. Influence of abdominal obesity

Abstract: To the Editor. The association between high red blood cell distribution width (RDW) and cardiovascular events and heart failure has been reported [4,7]. The link between elevated RDW and cardiovascular disease (CVD) risk may be due to an underlying chronic inflammation mediated by proinflammatory cytokines that could influence erythrocyte maturation [4]. The metabolic syndrome (MS) is a chronic inflammatory disorder that increases the risk of cardiovascular events and death [5]. A recent study [6] has found an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
8
1
1
Order By: Relevance
“…Laufer et al [29] demonstrated that high RDW (RDW ≥ 14%) was associated with increased risk of MS and long-term mortality, which also showed that hypertension was the strongest risk factor with RDW ≥ 14% in all criteria for MS. These results were not in good conformity with the study from Vaya et al [14]. In addition, a different point of view raised in the study of Emamian et al [7] was that level of RDW was higher among normotensive individuals than hypertensive.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Laufer et al [29] demonstrated that high RDW (RDW ≥ 14%) was associated with increased risk of MS and long-term mortality, which also showed that hypertension was the strongest risk factor with RDW ≥ 14% in all criteria for MS. These results were not in good conformity with the study from Vaya et al [14]. In addition, a different point of view raised in the study of Emamian et al [7] was that level of RDW was higher among normotensive individuals than hypertensive.…”
Section: Discussioncontrasting
confidence: 65%
“…The limitation of this study was that the number of samples (300 subjects) was too small to carry out subgroup analysis. In 2011, Vaya et al [14] pointed out that abdominal obesity was the only MS component associated with high RDW. However, Fujita et al [9] concluded that obesity was not necessarily positively correlated with RDW through animal models.…”
Section: Discussionmentioning
confidence: 99%
“… 8 9 Numerous investigators previously reported that erythrocyte parameters, including red blood cell (RBC) count, haematocrit (HCT), haemoglobin (Hb) and red blood cell distribution width (RDW) were positively associated with insulin resistance and chronic low grade inflammation. 10–14 In fact, RBC, 14–16 HCT, 15 16 Hb 14 15 17 and RDW 18 were demonstrated in several studies worldwide to correlate with MetS in adults. However, the association between erythrocyte parameters and MetS remains controversial, because the results reported are inconsistent depending on the different ethnic populations studied.…”
Section: Introductionmentioning
confidence: 97%
“…In a recent article on unselected outpatients from a general population, Lippi et al 25 observed that RDW was negatively associated with high-density lipoprotein cholesterol and positively associated with the atherogenic index of plasma. In this sense, Vayá et al 26 and Sánchez-Chaparro et al 27 found an association of RDW with metabolic syndrome and others with obesity, 24,28 hypertension, 29 and diabetes. 30 Given that CS affects a young population, and since we did not observe significant differences in the prevalence of cardiovascular risk factors (except higher obesity), the lack of correlation between RDW and plasmatic lipids is not surprising.…”
Section: Discussionmentioning
confidence: 95%